Suicidal ideation and intentional self-harm in pregnancy as a neglected agenda in maternal health; an experience from rural Sri Lanka - Arachchi, Nimna Sachini Malawara (Reprod Health, 2019)
BACKGROUND: Suicide only present the tip of the iceberg of maternal mental health issues. Only a fraction of pregnant women with suicidal ideation proceeds to intentional self-harm (ISH) and even a smaller proportion are fatal. The purpose of the present study was to determine the prevalence of depression, suicidal ideation (present and past) and history of ISH among pregnant mothers in rural Sri Lanka. METHODS: We have conducted a hospital based cross sectional study in the third largest hospital in Sri Lanka and an another tertiary care center. Pregnant women admitted to hospital at term were included as study participants. The Edinburgh Postpartum Depression Scale (EPDS), a self-administered questionnaire for demographic and clinical data and a data extraction sheet to get pregnancy related data from the pregnancy record was used. RESULTS: The study sample consisted of 475 pregnant women in their third trimester. For the tenth question of EPDS “the thought of harming myself has occurred to me during last seven days” was answered as “yes quite a lot” by four (0.8%), “yes sometimes” by eleven (2.3%) and hardly ever by 13 (2.7%). Two additional pregnant women reported that they had suicidal ideation during the early part of the current pregnancy period though they are not having it now. Four (0.8%) pregnant women reported having a history of ISH during the current pregnancy. History of ISH prior to this pregnancy was reported by eight women and five of them were reported to hospitals, while others were managed at home. Of the 475 pregnant females included in the study, 126 (26.5%) had an EPDS score more than nine, showing probable anxiety and depression. Pregnant women who had primary/post-primary or tertiary education compared to those who were in-between those two categories were at higher risk of high EPDS score with a OR of 1.94 (95% CI 1.1–3.3). Reported suicidal ideation prior to pregnancy was also associated with high EPDS with a OR of 6.4 (95% CI 2.3–17.5). CONCLUSIONS: Based on our data, we conservatively estimate around 500 pregnant women each year having suicidal ideation and, 130 ISH annually in Anuradhapura, which should be considered as a high priority for an urgent intervention.